Blood group antigen A type 3 expression is a favorable prognostic factor in advanced NSCLC. (February 2016) - Schmidt, L.H.; Kuemmel, A.; Schliemann, C.; Schulze, A.; Humberg, J.; Mohr, M.; Görlich, D.; Hartmann, W.; Bröckling, S.; Marra, A.; Hillejan, L.; Goletz, S.; et al.
Highlights: A type 3 is expressed on A1 erythrocytes and in NSCLC tissues of patients blood group A1 . No prognostic effect for A type 1/2 antigen. Favorable prognostic effect of A type 3 in advanced NSCLC patients. Multivariate Cox proportional hazards model confirms univariate results. Abstract: Objectives: Several blood group-related carbohydrate antigens are prognosis-relevant markers of tumor tissues. A type 3 (repetitive A) is a blood group antigen specific for A1 erythrocytes. Its potential expression in tumor tissues has so far not been examined. Material and methods: We have evaluated its expression in normal lung and in lung cancer using a novel antibody (A69-A/E8). For comparison an anti-A antibody specific to A types 1 and 2 was used, because its expression on lung cancer tissue has been previously reported to be of prognostic relevance. Resected tissue samples of 398 NSCLC patients were analyzed in immunohistochemistry using tissue microarrays. Results and conclusions: Expression of A type 3 was not observed in non-malignant lung tissues. A type 3 was expressed on tumor cells of around half of NSCLC patients of blood group A1 ( p  < 0.001). Whereas no prognostic effect for A type 1/2 antigen was observed ( p  = 0.562), the expression of A type 3 by tumor cells indicated a highly significant favorable prognosis among advanced NSCLC patients ( p  = 0.011) and in NSCLC patients with lymphatic spread ( p  = 0.014). Univariate prognostic results were confirmed in a Cox proportional hazards model. In this study we present for the first time prognostic data for A type 3 antigen expression in lung cancer patients. Prospective studies should be performed to confirm the prognostic value of A type 3 expression for an improved risk stratification in NSCLC patients.